1997
DOI: 10.1002/(sici)1097-4636(19970615)35:4<531::aid-jbm13>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Factors which affect the calcification of tissue-derived bioprostheses

Abstract: Mineralization of implanted bioprostheses poses a major clinical problem. Crosslinking of collagenous matrices, a process used to render tissues relatively inert and nonbiodegradable, seems to encourage calcification. Residual, noncovalently bound glutaraldehyde, as well as glutaraldehyde crosslinks which can be degraded with time, seem to play a role in this connection. Our findings demonstrate the need to carefully remove noncovalently or labile-associated glutaraldehyde by thorough rinsing or neutralization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…This high ratio suggests that calcification did not show poorly crystalline hydroxyapatite generally seen in BHV calcification in these groups. It has been suggested that reduction of free aldehydes by sodium borohydride in glutaraldehyde crosslinked tissues reduces calcification38 but we did not see any difference in the present study. Many of the previous studies included other neutralizing agents such as glutamic acid or L ‐lysine in addition to NaBH 4 that may have affected calcification 39.…”
Section: Resultscontrasting
confidence: 87%
“…This high ratio suggests that calcification did not show poorly crystalline hydroxyapatite generally seen in BHV calcification in these groups. It has been suggested that reduction of free aldehydes by sodium borohydride in glutaraldehyde crosslinked tissues reduces calcification38 but we did not see any difference in the present study. Many of the previous studies included other neutralizing agents such as glutamic acid or L ‐lysine in addition to NaBH 4 that may have affected calcification 39.…”
Section: Resultscontrasting
confidence: 87%
“…The most extended commercial chemical modification of biological tissues is GA crosslinking; however, this treatment is one of the major causes for clinical failure of bioprosthetic tissues combined with deposition of proteins and lipids and mechanical stress. Several authors have demonstrated that GA treatment induces an structural deterioration of collagen molecules and promotes GAGs extraction, both processes being probably linked to an increased calcification [7,26].…”
Section: Discussionmentioning
confidence: 99%
“…Calcification of degenerative type does, in fact, affect over 50% of glutaraldehyde-treated porcine aortic valves implanted in young patients, and from 5-10% of those implanted in adults, 5-10 years after implantation . In addition, because bioprosthetic valves are fixed with glutaraldehyde to improve their durability and make them less biodegradable, a number of studies have been carried out to detect the role this type of fixation may have in promoting valve calcification (Grabenwoger et al 1996;Nimni et al 1997), its effects on intracellular calcium and phosphate concentration (Kim et al 1999;Kim 2001), and the changes it may induce in the molecular tissue configuration (Girardot et al 1995). Obviously, this potentially highly dangerous process has repeatedly been studied to determine the role of the host metabolism, the effect of the mechanical forces involved and -the question most pertinent to the aims of this book -which of the valve components is locally responsible for the calcification process.…”
Section: Calcification Of Implanted Cardiac Bioprosthetic Valvesmentioning
confidence: 99%